A technical analysis of synchronized swimming competitions in the 9th national games - Chen, A.; Li, Z.; He, B.; Chen, L.; Liu, J.; Li, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
After the 8th National Games, there witnessed a great progress in Chinese synchronized swimming. Many data have come up to the world level. However, there still exist many problems and weak points, needed to take further measures to overcome in future training and only by this specific training can great achievements be made